2021
DOI: 10.3390/ijms22031366
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia annua L. Polyphenol-Induced Cell Death Is ROS-Independently Enhanced by Inhibition of JNK in HCT116 Colorectal Cancer Cells

Abstract: c-Jun N-terminal kinase (JNK) is activated by chemotherapeutic reagents including natural plant polyphenols, and cell fate is determined by activated phospho-JNK as survival or death depending on stimuli and cell types. The purpose of this study was to elucidate the role of JNK on the anticancer effects of the Korean plant Artemisia annua L. (pKAL) polyphenols in p53 wild-type HCT116 human colorectal cancer cells. Cell morphology, protein expression levels, apoptosis/necrosis, reactive oxygen species (ROS), ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Studies have shown that AA phyto-extracts, particularly ART and its analogues, have therapeutic effects on a variety of tumors and immune-related disorders. The mitogenactivated protein kinase (MAPK) pathway could be involved in these beneficial properties by regulating inflammatory response, cell cycle development, and apoptosis processes [47,53]. Cells are able to recognize the specific patterns of conserved molecular motifs associated with microbial pathogens (e.g., LPS) through the toll-like receptor (TLR) family, whose members are highly conserved glycoprotein receptors.…”
Section: Biological Activity Of Phyto-extractsmentioning
confidence: 99%
“…Studies have shown that AA phyto-extracts, particularly ART and its analogues, have therapeutic effects on a variety of tumors and immune-related disorders. The mitogenactivated protein kinase (MAPK) pathway could be involved in these beneficial properties by regulating inflammatory response, cell cycle development, and apoptosis processes [47,53]. Cells are able to recognize the specific patterns of conserved molecular motifs associated with microbial pathogens (e.g., LPS) through the toll-like receptor (TLR) family, whose members are highly conserved glycoprotein receptors.…”
Section: Biological Activity Of Phyto-extractsmentioning
confidence: 99%
“…AW (Artemisia annua L.) is a common type of wormwood native to temperate Asia but naturalized worldwide and belonging to the family Asteraceae [15]. Its bioactive derivatives control ROS, DNA damage, DNA repair, cell cycle arrest, apoptosis, inflammatory response, angiogenesis, and multiple signaling pathways, showing an anti-cancer effect [38]. In addition, it has an anti-hyperglycemic effect and reduces insulin resistance by increasing adiponectin secretion in adipocytes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Some metabolites showed different patterns for each fermented group. Unlike the GF group, the AF group showed a decrease in casticin (37) and an increase in pyroglutamyl-valine (1), pyroglutamyl-leucine (2), lactotyl-tryptophan (3), hydroxyglutaric acid (5), dihydrocaffeic acid (13), scopoletin (17), phloretic acid (19), 3-caffeoylquinic acid (21), 3,4-dicaffeoylquinic acid (23), 3-feruloyl-4-caffeoylquinic acid (24), hydroxybenzoic acid (30), syringic aldehyde (33), 4-ethylcatechol (32), 4-vinylcatechol (31), shikimic acid (38), and two non-identified metabolites (40,42) (Figure 2C). Relatedly, 9-DiHODE (8), 9,10-DiHOME (9), and N.I 2 (41) increased only in SF (Figure 2D).…”
Section: Relative Metabolite Abundance In Annual Wormwood and Glasswo...mentioning
confidence: 99%
“…Breast, liver, colon Prostate, Lung, Gastric (Tian et al, 2017); (Shati et al, 2020) Teucrium polium Glioblastoma, colon, melanoma, lung, breast (Khazaei et al, 2018) Linum usitatissimum Prostate, breast, colon, skin (Sharma et al, 2014); (Calado et al, 2018); (DeLuca et al, 2018); (Zhou et al, 2020) Artemisia annua Breast, colon, lung (Rassias and Weathers, 2019); (Ko et al, 2020); (Jung et al, 2021) Commiphora molmol Liver, cervix (Ramadan et al, 2017); (Anwar et al, 2021) Zingiber officinale Leukemia, prostate, breast, skin, ovarian, (Semwal et al, 2015); (Salehi et al, 2019) lung, pancreatic, colorectal…”
Section: Saussurea Costusmentioning
confidence: 99%